Image splicing forgery approachs: A review and future direction - Ernawati, Muji; Ernawan, Ferda; Abbker, Yagoub; Fakhreldin, Mohammad Adam Ibrahim; Adi, Prajanto Wahyu (Institute of Electrical and Electronics Engineers Inc., 2022)
With advances in image editing tools, attempts have been made to modify images, the altered image cannot be distinguished. This paper examines various approaches to image splicing forgery, discusses the weakness of methods, analyse the existing methods, and discusses the current solution to solve those issues, and future direction. This paper presents existing datasets, pre-processing techniques, feature extraction techniques, and classification algorithms that have been used in image splicing. This paper suggests some recommendations for future research which focuses on image localization, pre-processing, and feature extraction to improve accuracy in detecting image splicing forgery.